Children with developmental dyslexia showed greater sleep disturbances than controls, including problems initiating and maintaining sleep. (8th June 2016) - Carotenuto, M; Esposito, M; Cortese, S; Laino, D; Verrotti, A
Abstract: Aim: Although there have been frequent clinical reports about sleep disturbances in children with learning disabilities, no data are available about the prevalence of sleep disturbances in children with developmental dyslexia (DD). This study evaluated sleep disturbances in children with DD referred to a hospital clinic and compared their scores with healthy controls. Methods: We consecutively enrolled 147 children (66% male) aged 10.26 ± 2.63 years who were referred by clinical paediatricians to the Clinic for Child and Adolescent Neuropsychiatry at the Second University of Naples with DD and 766 children without DD (60% male) aged 10.49 ± 2.39 years recruited from schools in the same urban area. Sleep disturbances were assessed with the Sleep Disturbances Scale for Children (SDSC), which was filled out by the children's main carers. Results: Compared with the controls, the children with DD showed significantly higher rates of above threshold scores on the total SDSC score (p < 0.001) and on the subscales for disorders in initiating and maintaining sleep (p < 0.001), sleep breathing disorders (p < 0.001) and disorders of arousal (p < 0.001). Conclusion: Sleep disorders were significantly more frequent in children with DD than in healthy controls. A possible relationship between dyslexia and sleep disorders may have relevant clinical implications. Abstract :